How Commodity Prices Influence the Members of the Eurasian Economic Union - Polbin, Andrey Vladimirovich; Andreyev, Mikhail Yuryevich; Zubarev, Andrey Vitalyevich (Economy of Regions, 2018)
This paper tests the hypothesis on the presence of common factors in the dynamics of the Eurasian Economic Union (EAEU) countries' macroeconomic indicators. As the most important factor, the common dynamics of commodity prices in world markets was chosen. We identified key channels of the transmission of commodity price shocks for EAEU economies. Wiese transmission channels include both direct transmission channels, connected with the terms of trade, and indirect channels. We latter ones include labour migration between EAEU countries, money transactions by migrants, high trade linkages between EAEU countries, and preferential pricing for energy resources. We empirical part of the paper studies the influence of commodity prices on EAEU countries' macroeconomic indicators. We have proposed a factor autoregressive model. Based on this model, we have identified the first principal component price movements in oil, natural gas, aluminum, copper, steel, gold and wheat. We first principal component explains 75 % of oil and gas price growth rate variation, 45 % of the copper price growth rate variation, and more than 25 % of the variation of other series. Further, we used VAR model to estimate the influence of the first principal component on the EAEU countries' GDP, consumption and investment dynamics. We results showed the significant positive effect of commodity prices growth in all EAEU members. We also revealed a number of shock transmission features. For example, price shock affected Russian economy through the income effect, while the same shock affected Armenian economy through the direct output stimulation. Our results may be useful for the coordination of the economic policy and business cycles stabilization amongst EAEU countries.